Pembuatan Video Pelayanan Sebagai Media Informasi Menggunakan Adobe After Effect dan Adobe Premiere Pro: Studi Kasus Kantor Kelurahan Pungkur Kota Bandung - Anita, Nina; Sumarni, Tarsinah (Melati Institute, 2024)
The development of information technology today forces us into a digital era where everything is computerized. Utilization of digital technology can facilitate the delivery of information, the results can affect the quality of service information systems. Delivery of service information through video media can affect the quality of service, as well as alternative information that can be offered to the public. The making of service videos at the pungkur village office is used as one of the information providers for the community. The process of making service videos uses Adobe After Effect and Adobe Premiere Pro applications. This research aims to produce information related to services for the community, regarding various kinds of information related to services at the pungkur urban village office. The use of video media is expected to facilitate the delivery of information to the public regarding information related to this service. The utilization of information through the making of this video is expected to help people who need more information related to the service process.